Active and healthy ageing. Educational experience through intergenerational education - Coromoto Linares Baeza, Lorena; Roz Faraco, Carmen Cecilia; Martínez-Heredia, Nazaret (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This article purposes to describe intergenerational education experiences between 3 to 6 years old preschoolers and older people. Through the establishment of exchange- oriented links of appreciation and affective interrelation. These links contribute to revitalize the activity of those who have developed a long life experience, making them to feel useful, updated and less prone to suffer diseases, through the experience of intergenerational education “Grandparents’ Circle” de-veloped in the Padre Machado Educational Complex, attached to the Mayor’s Office of the Municipality of San Diego in the city of Valencia, Carabobo State, Venezuela.